1999
DOI: 10.1126/science.285.5424.96
|View full text |Cite
|
Sign up to set email alerts
|

A Phospholipase C-Dependent Inositol Polyphosphate Kinase Pathway Required for Efficient Messenger RNA Export

Abstract: In order to identify additional factors required for nuclear export of messenger RNA, a genetic screen was conducted with a yeast mutant deficient in a factor Gle1p, which associates with the nuclear pore complex (NPC). The three genes identified encode phospholipase C and two potential inositol polyphosphate kinases. Together, these constitute a signaling pathway from phosphatidylinositol 4, 5-bisphosphate to inositol hexakisphosphate (IP6). The common downstream effects of mutations in each component were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
542
3
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 493 publications
(559 citation statements)
references
References 25 publications
12
542
3
2
Order By: Relevance
“…Inositol phosphates and the regulation of nuclear mRNA export Recently, York et al [5] described a mutant strain of yeast, named gsl3, that displayed changes in inositol phosphate turnover that, in some cases, are similar to those of our ipmkv strain. These include decreases in levels of InsP 6 , accompanied by increases in levels of InsP 2 , Ins(1,4,5)P 3 and InsP 4 [5].…”
Section: Analysis Of Ipmk Activity In Vitromentioning
confidence: 66%
See 3 more Smart Citations
“…Inositol phosphates and the regulation of nuclear mRNA export Recently, York et al [5] described a mutant strain of yeast, named gsl3, that displayed changes in inositol phosphate turnover that, in some cases, are similar to those of our ipmkv strain. These include decreases in levels of InsP 6 , accompanied by increases in levels of InsP 2 , Ins(1,4,5)P 3 and InsP 4 [5].…”
Section: Analysis Of Ipmk Activity In Vitromentioning
confidence: 66%
“…Inositol phosphates and the regulation of nuclear mRNA export Recently, York et al [5] described a mutant strain of yeast, named gsl3, that displayed changes in inositol phosphate turnover that, in some cases, are similar to those of our ipmkv strain. These include decreases in levels of InsP 6 , accompanied by increases in levels of InsP 2 , Ins(1,4,5)P 3 and InsP 4 [5]. The protein product that was disrupted in the gsl3 strain was not identi¢ed, although it was suggested that it might be either (i) a regulator of kinase activities against InsP 3 and InsP 4 , or (ii) a multifunctional InsP 3 /InsP 4 kinase [5].…”
Section: Analysis Of Ipmk Activity In Vitromentioning
confidence: 66%
See 2 more Smart Citations
“…In yeast, IP 6 affects mRNA export from the nucleus. 107 Another possibility is that higher order InsPs directly change gene promoter activity. In yeast, the genes encoding inositol synthase (ino-1) and the phosphate response gene pho5 are regulated through changes in ATPdependent chromatin remodeling complexes.…”
Section: Gene Expressionmentioning
confidence: 99%